2019
DOI: 10.1093/intimm/dxz050
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal dysbiosis mediates experimental autoimmune pancreatitis via activation of plasmacytoid dendritic cells

Abstract: Dysbiosis contributes to the development of autoimmune pancreatitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 62 publications
4
65
0
Order By: Relevance
“…Thus, these serum cytokine assays revealed that patients with type 1 AIP and IgG4-RD were characterized by elevated serum IFN-α and IL-33 concentrations. These serum cytokine data were fully consistent with our recent studies in which pDC-mediated production of IFN-α and IL-33 was shown to play a pathogenic role in the development of experimental AIP and human type 1 AIP 1,[15][16][17][18][19] .…”
Section: Profiles Of Serum Immunoglobulins Including Igg Subtypes Insupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, these serum cytokine assays revealed that patients with type 1 AIP and IgG4-RD were characterized by elevated serum IFN-α and IL-33 concentrations. These serum cytokine data were fully consistent with our recent studies in which pDC-mediated production of IFN-α and IL-33 was shown to play a pathogenic role in the development of experimental AIP and human type 1 AIP 1,[15][16][17][18][19] .…”
Section: Profiles Of Serum Immunoglobulins Including Igg Subtypes Insupporting
confidence: 92%
“…In addition, the induction of remission by PSL markedly lowered the serum concentrations of IgG4, IFN-α, and IL-33. As has been shown in previous reports, including our own, the activation of IFN-α and IL-33 is involved in the immunopathogenesis of experimental AIP and human type 1 AIP/IgG4-RD 1,[15][16][17][18][19]30,31 . However, the utility of serum IFN-α and IL-33 levels as biomarkers of type 1 AIP/IgG4-RD has never been evaluated.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations